2012
DOI: 10.1017/s1598240800008055
|View full text |Cite
|
Sign up to set email alerts
|

The Nationalization of Japanese Elections

Abstract: The postwar electoral dominance of the Liberal Democratic Party (LDP) was founded on (1) strong incumbency advantage, which insulated its legislators from declining party popularity, and (2) the malapportionment of districts, which overvalued the electoral clout of the party's rural base. The LDP's demise in 2009 was due to the reversal of both factors, each of which was related to electoral reforms in the 1990s. First, I demonstrate that elections are becoming more “nationalized,” due to the growing weight th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(22 citation statements)
references
References 22 publications
(24 reference statements)
0
21
0
Order By: Relevance
“…The literature on the recent elections in Japan suggests that party labels and the leadership's popularity now signiicantly inluence candidates' electoral fortunes (McElwain 2012;Patterson and Maeda 2007) and clientelism is now being replaced by programmatism (Rosenbluth and Thies 2010). Furthermore, in 2009 Japan had a government turnover through elections for the irst time in more than 60 years, because the combination of the DPJ's potential and disillusionment with the LDP government's policy performance convinced most swing voters: a poll on the 2009 turnover, for example, showed that 61.2% of voters thought party reputations were important in making voting decisions, compared to 29.0% who considered individual candidates' personal traits as important (Akarui Senkyo Suishin Kyōkai 2010).…”
Section: Kuniaki Nemoto and Chia-hung Tsaimentioning
confidence: 99%
“…The literature on the recent elections in Japan suggests that party labels and the leadership's popularity now signiicantly inluence candidates' electoral fortunes (McElwain 2012;Patterson and Maeda 2007) and clientelism is now being replaced by programmatism (Rosenbluth and Thies 2010). Furthermore, in 2009 Japan had a government turnover through elections for the irst time in more than 60 years, because the combination of the DPJ's potential and disillusionment with the LDP government's policy performance convinced most swing voters: a poll on the 2009 turnover, for example, showed that 61.2% of voters thought party reputations were important in making voting decisions, compared to 29.0% who considered individual candidates' personal traits as important (Akarui Senkyo Suishin Kyōkai 2010).…”
Section: Kuniaki Nemoto and Chia-hung Tsaimentioning
confidence: 99%
“…The situation is reminiscent of the past party system of dominance by the LDP and fragmented, weak opposition parties (Scheiner 2006). Japanese elections, especially the general (lower house) elections, have been nationalized since the introduction of the current electoral system and have shown a high level of volatility (McElwain 2012). High volatility in electoral outcomes and opposition party vulnerability has become quite a serious problem in Japanese politics.…”
Section: Research Questionsmentioning
confidence: 99%
“…His strong popularity among commoners led to his party's recovery of electoral strength, allowing him to maintain premiership for more than five years despite his weak factional bases. Party leaders' increased importance in electoral campaigning in turn results from the fact that the 1994 electoral reform has moved Japanese party politics closer to a two‐party system and pushed voters to make voting decisions based on the party rebel rather than candidates' personal appeals (McElwain, ; Rosenbluth & Thies, , pp. 113–115).…”
Section: Analyzing Causes Of Dpj's Failurementioning
confidence: 99%